Rigor and Viral Contents: an Impossible Couple in Science Communication? (2016)
For Antonio Calvo, rigorousness and virality or influence are not opposite or have to go separately, however, they require great work to make the news with scientific dissemination always rigorous, but also interesting for those who are not part of that field of study.